The Arab Journal of Forensic Sciences and Forensic Medicine (AJFSFM): A new era of sharing knowledge and research - Abdul Rauf Chaudhary Bashir (Arab Journal of Forensic Sciences & Forensic Medicine, 2014)
Education and research are indispensable tools for the scientific and economic growth of a nation, and it is of the greatest importance to have effective mechanisms which provide the academic and scientific community with the latest research and recent developments in their respective fields of expertise. This rapid broadcasting of scientific information not only facilitates their research but also contributes towards exciting new discoveries. Scientific journals and magazines are one of the best means to facilitate the dissemination of vital research and other information essential to the academic and scientific community. At present, there are more than 28,000 scholarly journals serving the scientific community, researchers, students, and professionals worldwide.